PENAMAAN “LUM” PADA KELOMPOK MASYARAKAT DINAMISME DI BANGKA BAGIAN UTARA: SEBUAH TINJAUAN SEMANTIK PRAGMATIK - Asrul Munazar (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
A proper name is not only an identity for people or things around but also organization and com- munity. The Processes behind naming are presented and explained in various ways to give the new insight of creating a name. This research deals with the lexicon of lum for naming used on groups of dynamism community. To explore the nature of lexical meaning, qualitative method was used in this research with descriptive approach. As an adverb class in Bangka language daily spoken, the lexicon was analysed by semantic pragmatics perspective to investigate the meaning of its name. The result showed that the lexicon of lum becomes a name for dinamism community as “lum tribe” originally has conotation meaning and increases missunderstanding problems among the community in Belinyu.